STUDENTS’ PERSONAL “COLORS” IN SELF-EVALUATION ESSAYS AS THE POST-PROCESS PEDAGOGY IN TEACHING WRITING (A DESCRIPTIVE STUDY ON EFL COMPOSITION LEARNING PRACTICE IN INDONESIA) - Syayid Sandi Sukandi (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Undoubtedly, teaching English requires thorough process of assessment. Such process usually, or traditionally, use the three stages: pre-teaching, whilst-teaching, and post-teaching. Thus, we tend to use rubric score and focus on how well students can cope with what we teach and how good they answer the questions we made in the final examination. At this point, we skip one important thing: the students’ voice on what they have learned. As such, this research aims to reach out the students’ personal “colors” as a way to see how far one teaches English writing. The theory used in framing this research is the post-process pedagogy. Meanwhile, the context is geared toward the activity of learning English as a Foreign Language in Indonesia, especially in Padang city. This research is closer to qualitative research with the method of analysis applied is document analysis. The purpose of analyzing students’ personal self-evaluation essays is to describe their “colors” after learning in the researcher’s class. The result of the analysis is that the students have their inclination to see our class through different ways, and therefore, they will firstly see us as the thing they see all the time, then the process of what they learn become the aspect they see. Students who are lack of critical thinking usually comment on the lecturer’s performance than the overall process of the classroom. The sequence of the self-evaluation and final score resemble that the connection of these two things remain intact within the view of post-process pedagogy.